Two-photon correlation of radiation emitted by two excited atoms: detailed analysis of a Dicke problem - Ooi, Chong Heng Raymond; Scully, M.O.; Rostovtsev, Y. (IOP Publishing, 2007)
A radiative interaction in a collective two-atom system forms subradiant and superradiant states when the distance between neighboring atoms is less than half a wavelength of resonant radiation. We calculate the G((2)) function depending on the atomic separation and detection angle and show that it oscillates with a time delay between two successively emitted photons. These oscillations are the signature of coherent effects due to the periodic emission and absorption of photons by each atom.